Formation and development of legal framework of the EAEU states-founders integration - Amirbek, K.S.; Lavnichak, A. (KSU Publ., 2018)
The present article addresses the task to examine the main questions of formation and development of the legal framework of the new Union Association of states – the Eurasian Economic Union (EAEU). The development of international economic integration is impossible without a legal basis, because it is through bilateral and multilateral treaties and also domestic legislation the states-participants of the international economic integration carried out in real life political solutions and ideas. Prospects of development of the Eurasian Economic Union require the analysis of new approaches to the integration interaction, as well as solutions of certain legal issues. First of all, it concerns the functioning of the legal support of both the EAEU, and the introduction of the acts of its bodies. Particular attention in this article is given to the solution of many legal problems in the framework of implementation of customs cooperation between the Union's Member States, as well as the adoption of national regulations, amendments and additions into the national law. The article states that it is necessary to clearly define the system of mutually views on their common objectives and priorities for the development of the legal framework of the Union in the sphere of customs by EAEU member states. The authors notes that these measures should be based on voluntary participation and independence of states in determining of the directions and depth of the participation in the processes of convergence, harmonization and unification of customs legislation.
ЕАЭО құрушы-мемлекеттерінің интеграциясының құқықтық базасының қалыптасуы мен дамуы
Формирование и развитие правовой базы интеграции государств-основателей ЕАЭС
Keywords: interstate economic integration; the Customs Union (CU); the Eurasian Economic Space (ЕES); the Eurasian Economic Community (EurAsEC) the Eurasian Economic Union (EAEU); the formation of legal base of the EAEU; the sources of EAEU law; international personality of the EAEU; he Customs Code of the EAEU (EAEU CC); the decisions of the Eurasian economic Commission